On Fixed and Variable Fiscal Surplus Rules. (IMF Working Papers; Working Paper ;, 2004)
Fiscal rules are being increasingly used by both emerging and developed economies. This paper analyzes two alternative fiscal policy rules in terms of their impact on debt sustainability: a rule that fixes the ratio of primary surplus to GDP ("fixed surplus rule") and one that sets the primary surplus as a linear function of debt to GDP ratio ("variable surplus rule"). A simple debt dynamics equation, incorporating real shocks, is constructed, and the probability of exceeding the critical debt level is simulated using Monte Carlo techniques. The results show that the variable surplus rule performs better than the simple fixed surplus rule, by reducing debt sustainability concerns and the necessary medium-term primary surplus. This result hinges on the government's ability to make a credible commitment to the variable surplus rule in the medium run.